Information System Design for Tadarus Madrasah Ibtidaiyah (MI) Darul Ulum Kintap Webbased - Suci Febriani; Herpendi; Muhammad Noor (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
Madrasah is a place of study or formal school equivalent to elementary school, but at madrasah there will be more to learn about Islam, especially learning to read the Koran. Madrasah Ibtidaiyah (MI) Kintap uses the at-tanzil method in the process of learning the Qur'an, with the aim that students can understand more quickly about tajwid and the law of reading the Quran. MI Darul Ulum Kintap will provide a notebook of the achievements of the students so that parents can monitor the extent to which the students have learned. The problem that exists in recording the student's achievement using a note book is the negligence of the students in maintaining the achievement record book, so that it can make it difficult for parents and teachers to monitor the learning process of the students. To overcome this problem, the authors take advantage of technological developments by building a system that can be used to access data on student achievement in real time. This research also adds a feature to register new students, so that parents can register their children online. In this research, data analysis uses the method waterfall. The results of the research that has been carried out are that all features or functions of the system built have run well according to their function by testing the functionality of the system using the method black-box.